2020
DOI: 10.1093/mnras/staa344
|View full text |Cite
|
Sign up to set email alerts
|

Overconstrained gravitational lens models and the Hubble constant

Abstract: It is well known that measurements of H 0 from gravitational lens time delays scale as H 0 ∝ 1 − κ E where κ E is the mean convergence at the Einstein radius R E but that all available lens data other than the delays provide no direct constraints on κ E . The properties of the radial mass distribution constrained by lens data are R E and the dimensionless quantityis the second derivative of the deflection profile at R E . Lens models with too few degrees of freedom, like power law models with densities ρ ∝ r −… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 48 publications
4
113
0
Order By: Relevance
“…The model parameters are given in Eqs. (7) and (8) for EDE and ΛCDM, respectively, corresponding to the best-fit parameters from Ref. [40] in the fit to primary CMB, CMB lensing, BAO, RSD, SNIa, and SH0ES data.…”
Section: Ede Meets Lssmentioning
confidence: 99%
See 3 more Smart Citations
“…The model parameters are given in Eqs. (7) and (8) for EDE and ΛCDM, respectively, corresponding to the best-fit parameters from Ref. [40] in the fit to primary CMB, CMB lensing, BAO, RSD, SNIa, and SH0ES data.…”
Section: Ede Meets Lssmentioning
confidence: 99%
“…For example, the physical cold dark matter density ω cdm increases by over 5% when going from ΛCDM to EDE best-fit parameters [see Eqs. (7) and (8)]. This increase is needed to compensate for the early-ISWinduced growth suppression caused by the EDE.…”
Section: Ede Meets Lssmentioning
confidence: 99%
See 2 more Smart Citations
“…Wong et al 2020). A number of authors have suggested that the currently employed SPL model lacks the freedom necessary to model accurately the lens mass when measuring H 0 (Xu et al 2016;Sonnenfeld 2018;Kochanek 2020). The consequence could be that measurements of H 0 , although precise, are inaccurate because of a biased measurement of the potential at the positions of the lensed images.…”
Section: Introductionmentioning
confidence: 99%